2018
DOI: 10.1039/c8cc07433j
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb repressive complex 2 binds RNA irrespective of stereochemistry

Abstract: The Polycomb Repressive Complex 2 (PRC2) interacts promiscuously with G-quadruplex (G4) RNA structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…For example, a positive correlation between G-quadruplex (G4) formation and cytotoxicity has been reported for G-rich D-DNA. 28 In the case of G-rich L-RNA, potent cytotoxicity was observed for both G4-forming sequences (e.g., L-r(GGAA) 8 ) and those that cannot fold into G4s (e.g., L-r(GA) 20 ) (Figure 2 and Table 1) 19 , suggesting that the cytotoxic effects are mostly independent of the potential for G4 formation. In support of this notion, we obtained circular dichroism spectra of two cytotoxic sequences L-r(GGAA) 8 and L-r(GA) 20 under conditions used during transfection (25 mM Tris pH 7.4, 1 mM EDTA, and 50 mM KCl in Opti-MEM), as well as under intracellular K + concentrations (140 mM KCl) (Figure S4).…”
Section: Cytotoxicity Of G-rich L-rnas Is Dependent On Structure and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a positive correlation between G-quadruplex (G4) formation and cytotoxicity has been reported for G-rich D-DNA. 28 In the case of G-rich L-RNA, potent cytotoxicity was observed for both G4-forming sequences (e.g., L-r(GGAA) 8 ) and those that cannot fold into G4s (e.g., L-r(GA) 20 ) (Figure 2 and Table 1) 19 , suggesting that the cytotoxic effects are mostly independent of the potential for G4 formation. In support of this notion, we obtained circular dichroism spectra of two cytotoxic sequences L-r(GGAA) 8 and L-r(GA) 20 under conditions used during transfection (25 mM Tris pH 7.4, 1 mM EDTA, and 50 mM KCl in Opti-MEM), as well as under intracellular K + concentrations (140 mM KCl) (Figure S4).…”
Section: Cytotoxicity Of G-rich L-rnas Is Dependent On Structure and ...mentioning
confidence: 99%
“…Indeed, we recently showed that l -RNA binds tightly to the polycomb repressive complex 2 (PRC2) and prevents it from interacting with its intended targets. 19 If l -oligonucleotides are to be routinely employed in living cells and organisms, then it is imperative that we understand how they interact with these environments and their potential consequences. Such studies may also reveal whether chirality as a design parameter can be harnessed to induce and/or modulate a desired biological response, opening the door to new applications.…”
Section: Introductionmentioning
confidence: 99%
“…Even l ‐ONs may not be immune to the effects of nonspecific protein binding. A recent study showed that the polycomb repressive complex 2, a promiscuous RNA‐binding protein and important epigenetic regulator, can bind l ‐ONs with high affinity, leading to altered function (Deckard & Sczepanski, 2018).…”
Section: Future Outlook and Perspectivesmentioning
confidence: 99%